أحكام الحكرة والإحتكار في معاملات المالية دراسة المقارنة بين أراء الفقهاء والمحدثين - Desmadi Saharudin (Universitas Islam Negeri Jakarta, 2015)
Trade transactions conducted to gain an advantage in bad ways is prohibited by Islamic Law. It is a sin or despotic practice when someone saves a commodity not to be sold and reduced the availability of existing goods market and cause the expensiveness of shortages. Then prices could also be rising because of increasing demand on certain commodities, even there is no scarcity.Someone is allowed to store his belongings to the extent desired time and then sell when the price is already more expensive in order to make a profit.DOI: 10.15408/ajis.v15i2.2870